Does Market Interaction Erode Moral Values? - Björn Bartling; Ernst Fehr; Yagiz Özdemir (The Review of Economics and Statistics, 2023)
The widespread use of markets leads to unprecedented material well-being in many societies. We study whether market interaction, as a side effect, erodes moral values. In an influential paper, Falk and Szech (2013) provide experimental data that seem to suggest that “market interaction erodes moral values.” Although we replicate their main treatment effect, we show that additional treatments are necessary to corroborate their conclusion. These treatments reveal that playing repeatedly, and not market interaction, causes the erosion of moral values. Our paper thus shows that neither Falk and Szech's data nor our data support the claim that markets erode morals.
Keywords: 330